Satellites quantify the spatial extent of cyanobacterial blooms across the United States at multiple scales. (July 2022) - Schaeffer, Blake A.; Urquhart, Erin; Coffer, Megan; Salls, Wilson; Stumpf, Richard P.; Loftin, Keith A.; Jeremy Werdell, P.
Highlights: National spatial extent increased from 2017 to 2020 but did not change from 2008 to 2011. Satellite measures were available for over 2, 000 larger lakes and reservoirs. Cyanobacterial spatial extent changes were dependent on spatial and temporal scales. Region, state, and lake scales show complex patterns of change in the U.S. A decrease, or no change, does not indicate a lack of cyanobacteria-related issues. Abstract: Previous studies indicate that cyanobacterial harmful algal bloom (cyanoHAB) frequency, extent, and magnitude have increased globally over the past few decades. However, little quantitative capability is available to assess these metrics of cyanoHABs across broad geographic scales and at regular intervals. Here, the spatial extent was quantified from a cyanobacteria algorithm applied to two European Space Agency satellite platforms—the MEdium Resolution Imaging Spectrometer (MERIS) onboard Envisat and the Ocean and Land Colour Instrument (OLCI) onboard Sentinel-3. CyanoHAB spatial extent was defined for each geographic area as the percentage of valid satellite pixels that exhibited cyanobacteria above the detection limit of the satellite sensor. This study quantified cyanoHAB spatial extent for over 2, 000 large lakes and reservoirs across the contiguous United States (CONUS) during two time periods: 2008–2011 via MERIS and 2017–2020 via OLCI when cloud-, ice-, and snow-free imagery was available. Approximately 56% of resolvable lakes were glaciated, 13% were headwater, isolated, or terminal lakes, and the rest were primarily drainage lakes. Results were summarized at national-, regional-, state-, and lake-scales, where regions were defined as nine climate regions which represent climatically consistent states. As measured by satellite, changes in national cyanoHAB extent did have a strong increase of 6.9% from 2017 to 2020 (|Kendall's tau (τ)| = 0.56; gamma ( γ ) = 2.87 years), but had negligible change (| τ | = 0.03) from 2008 to 2011. Two of the nine regions had moderate (0.3 ≤ | τ | < 0.5) increases in spatial extent from 2017 to 2020, and eight of nine regions had negligible (| τ | < 0.2) change from 2008 to 2011. Twelve states had a strong or moderate increase from 2017 to 2020 (| τ | ≥ 0.3), while only one state had a moderate increase and two states had a moderate decrease from 2008 to 2011. A decrease, or no change, in cyanoHAB spatial extent did not indicate a lack of issues related to cyanoHABs. Sensitivity results of randomly omitted daily CONUS scenes confirm that even with reduced data availability during a short four-year temporal assessment, the direction and strength of the changes in spatial extent remained consistent. We present the first set of national maps of lake cyanoHAB spatial extent across CONUS and demonstrate an approach for quantifying past and future changes at multiple spatial scales. Results presented here provide water quality managers information regarding current cyanoHAB spatial extent and quantify rates of change.